Analisis Kesulitan Pelafalan Kosakata Bahasa Inggris Siswa Kelas V SDN Pondok Makmur - Saridevita, Alviani; Suhendar, Asep; Hasan, Najib (ANWARUL, 2022)
The importance of English to be learned in this era of globalization, it would be better if English is taught early on. The earlier you get to know a foreign language, the easier it is to develop your skills. The focus of this research is some students who have difficulty pronouncing English vocabulary in class V SDN Pondok Makmur. The purpose of this study was to describe the difficulty of pronouncing English vocabulary for the fifth grade students of SDN Pondok Makmur. The type of research method used is a type of qualitative descriptive analysis research method, namely the researcher will describe the difficulty of pronouncing English vocabulary for the fifth grade students of SDN Pondok Makmur, Tangerang City. Data collection techniques using tests, observations and documentation. Students found difficulty in pronouncing vocabulary from the results of this research test, there were errors of consonants as many as 4 words, vowels 3 words, intonation 10 words, and word stress 27 words. The most dominant errors are on word stress, second intonation, third consonants, and lastly on vowels.